2009
DOI: 10.1590/s0073-47212009000200001
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclis peruvianus (Gastropoda, Acavidae), an endemic land snail from Chile

Abstract: ABSTRACT. Macrocyclis peruvianus (Lamarck, 1822) is a large terrestrial snail which is endemic in Chile. A detailed description of its shell structure, jaw, radula, palial cavity and reproductive system is presented here for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In addition, Macrocyclis peruvianus is commonly associated with different forest types, both in the coastal and Andean ranges (Gómez et al, 2020;Valdovinos & Stuardo, 1988). Their microhabitat is composed mainly of leaf litter, ferns, mosses, decaying deadwood and a dense understory (Silva & Thomé, 2009). Other natural history and ecological notes of this spectacular native gastropod have been collected over time by Barahona-Segovia et al (2019), Gómez et al (2020), and, more recently, Boll et al (2023), who described the predation of Polycladus gayi (Tricladida: Geoplanidae) on M. peruvianus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Macrocyclis peruvianus is commonly associated with different forest types, both in the coastal and Andean ranges (Gómez et al, 2020;Valdovinos & Stuardo, 1988). Their microhabitat is composed mainly of leaf litter, ferns, mosses, decaying deadwood and a dense understory (Silva & Thomé, 2009). Other natural history and ecological notes of this spectacular native gastropod have been collected over time by Barahona-Segovia et al (2019), Gómez et al (2020), and, more recently, Boll et al (2023), who described the predation of Polycladus gayi (Tricladida: Geoplanidae) on M. peruvianus.…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with healthy cordilleran and coastal forests (Gómez et al, 2020), found in the forest soil among ferns, moss, liverworts and even under fallen logs (Silva & Thomé, 2009). The shell is recognizable by its shape and size: depressed, with whorls rapidly increasing in size, reaching 50–60 mm in diameter (Salvador et al, 2021; Silva & Thomé, 2009). Similar to the case of P. gayi and other invertebrates of Chilean forests, the ecology of M. peruvianus is poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…This snail is found in Chile, between the Maule and Aysén regions, and in neighbouring areas of Argentina, in the Neuquén province and the Bariloche department of the Río Negro province, overlapping with the known distribution of P. gayi (Barahona‐Segovia, 2019; Salvador et al, 2021). It is associated with healthy cordilleran and coastal forests (Gómez et al, 2020), found in the forest soil among ferns, moss, liverworts and even under fallen logs (Silva & Thomé, 2009). The shell is recognizable by its shape and size: depressed, with whorls rapidly increasing in size, reaching 50–60 mm in diameter (Salvador et al, 2021; Silva & Thomé, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Chile, land snails are one of the least studied molluscan groups; apart from the early works describing species in the ninetenth century ( Broderip & Sowerby, 1832a ; Broderip & Sowerby, 1832b ; King & Broderip, 1832 ; Sowerby, 1833 ; D’Orbigny, 1834–1847 ; D’Orbigny, 1835 ; Anton, 1838 ; Pfeiffer, 1842 ; Pfeiffer, 1847 ; Souleyet, 1842 ; Reeve, 1848–1850 ; Hupé, 1854 , among others), and of a few works in the twentieth century ( Odhner, 1922 ; Odhner, 1963 ; Gigoux, 1932 ; Rehder, 1945 ; Biese, 1949 ; Biese, 1960 ; Herm, 1970 ; Tillier, 1981 ), the last major revision listed 154 species of terrestrial molluscs occurring in the country ( Stuardo & Vega, 1985 ). Further works only include a bibliographical publication on Bulimulidae ( Stuardo & Valdovinos, 1985 ), a detailed revision of the genus Plectostylus ( Valdovinos & Stuardo, 1988 ), the revision of the families Veronicellidae, Pupillidae and Achatinellidae occurring in the country ( Stuardo & Vargas-Almonacid, 2000 ), a study of the endemic slug Phyllocaulis gayi ( Fischer, 1871 ) ( Simonetti, Grez & Bustamante, 2003 ), of a charopid and an endemic acavid species ( Cádiz & Gallardo, 2008 ; Silva & Thomé, 2009 ), and the description of a few new species, all of them charopid or endodontid micromollusks ( Valdovinos & Stuardo, 1989 ; Vargas-Almonacid, 2000 ; Vargas-Almonacid & Stuardo, 2007 ; Miquel & Barker, 2009 ; Miquel & Cádiz-Lorca, 2008 ; Araya & Aliaga, 2015a ), and a sub fossil Achatinellid from Easter Island ( Kirch, Christensen & Steadman, 2009 ). Land Mollusca from northern Chile in particular were studied in greatest depth by Pilsbry in his monumental treatise of the pulmonate Mollusca ( Pilsbry, 1895–1896 ).…”
Section: Introductionmentioning
confidence: 99%